Investigation of the effect of 12-week exercise training on the level of physical fitness in children with autism - Bilal Karakoc (Ozlem Book Center, 2023)
The aim of this study is to investigate the effect of 12-week exercise training on the level of physical fitness in autistic children. A total of 10 individuals, 4 females and 6 males, residing in Çanakkale city center and having autism are included in the study. The age range of individuals participating in the study is 13-19. These individuals were reached through previous volunteer projects and Kepez Special Education Vocational School. Studies were conducted 2 days a week, Monday - Thursday, for 12 weeks. The studies were conducted between 40 and 55 minutes, depending on the content of the study. Particular attention was paid to the safety and health aspects of the studies. Students studying at the Faculty of Sports Sciences supported the studies voluntarily. Various tests are used to scale the physical parameters as a data collection tool in the study. In the analysis of the data, normality test and reliability test results were examined and it was determined that the data conformed to normal distribution wand was reliable. Based on this point, parametric testing techniques were used to test the data. Differences between pretest and posttest mean values were performed using Paired Groups T Test. According to the results obtained, it is concluded that there is no statistically significant difference between the height, weight, flexibility, biceps, triceps, suprailiac and suspcapula pre-test and post-test mean values of the male and female participants.